Civil Liability For Breaches in Sale and Purchase Agreements and Their Impact on Consumer Protection - Rifdhan Ismeth Nyandra; Gunawan Djajaputra (Trunojoyo Madura University, 2025)
Sale and purchase agreements are among the most frequently used forms of engagement in various community activities, both for simple and high-value transactions. Although the Civil Code provides a clear legal basis, particularly regarding the parties' obligations and the consequences of default, practice shows that breaches of agreement still occur frequently and have a direct impact on consumer losses. In digital transactions, forms of default become more diverse due to technical factors, inaccurate information, and the presence of third parties, such as marketplace platforms. The classical legal framework in the Civil Code, including Articles 1238 and 1243, has not been fully able to answer the complexity of modern digital transactions. On the other hand, regulations such as the Consumer Protection Law, the ITE Law, and PP 71/2019 provide strengthening, but have not been systematically integrated with the concept of default. This research aims to fill this gap by analyzing civil liability for default in the context of conventional and digital transactions, using normative legal research methods, with a statutory and case approach. The results show the need for regulatory harmonization to strengthen consumers' position and provide legal certainty in the event of defaults, especially in transactions involving electronic technology and systems.